Hubungan Status Gizi dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Bajayau - Rahmi; Hapisah; Isnaniah; Suhrawardi (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Background: Anemia in pregnant women is a serious health issue that increases the risk of complications such as hemorrhage, preterm birth, and low birth weight. Poor nutritional status is a significant risk factor for anemia in pregnant women. The purpose of this study was to analyze the relationship between nutritional status and the incidence of anemia in pregnant women in the working area of Bajayau Health Center. Methods: This case-control study with a involving a sample of 57 pregnant women registered at the Bajayau Health Center in 2024, including 19 anemic pregnant women (case group) and 38 non-anemic pregnant women (control group). Data were collected from health records and analyzed using Chi-Square test with SPSS. Results: A significant relationship was found between nutritional status and anemia incidence in pregnant women with p=0.000 and an Odds Ratio (OR) of 19.950, indicating that pregnant women with poor nutritional status were 19 times more likely to experience anemia. Conclusion: Nutritional status is closely associated with the incidence of anemia in pregnant women in the working area of Bajayau Health Center, highlighting the need for improved nutritional monitoring and education to prevent anemia. Abstrak Latar belakang: Anemia pada ibu hamil merupakan masalah kesehatan serius yang dapat menambah risiko komplikasi selama kehamilan, seperti perdarahan, kelahiran prematur, dan bayi berat lahir rendah. Status gizi yang buruk dapat meningkatkan risiko kejadian anemia pada ibu hamil. Tujuan penelitian ini adalah untuk menganalisis hubungan antara status gizi dengan kejadian anemia pada ibu hamil di wilayah kerja Puskesmas Bajayau. Metode: Penelitian ini menggunakan desain case-control dengan pendekatan retrospektif, melibatkan sampel sebanyak 57 ibu hamil yang tercatat di Puskesmas Bajayau pada tahun 2024, yang terdiri dari 19 ibu hamil dengan anemia (kelompok kasus) dan 38 ibu hamil tanpa anemia (kelompok kontrol). Data dikumpulkan melalui catatan kesehatan dan dianalisis dengan uji Chi-Square menggunakan SPSS. Hasil: Terdapat hubungan signifikan antara status gizi dengan kejadian anemia pada ibu hamil dengan nilai p=0,000 dan Odds Ratio (OR) 19,950, yang menunjukkan ibu hamil dengan status gizi kurang berisiko 19 kali lebih besar mengalami anemia. Kesimpulan: Status gizi berhubungan erat dengan kejadian anemia pada ibu hamil di wilayah kerja Puskesmas Bajayau, sehingga diperlukan upaya peningkatan pemantauan gizi dan edukasi bagi ibu hamil untuk mencegah anemia. Kata kunci: Status gizi, anemia, ibu hamil, Puskesmas Bajayau